Simulation analysis of energy absorption capacity of 3D printed structure design - Goi, Chin Yong (Nanyang Technological University, 2023)
In this study, the energy absorption capabilities of a kirigami-inspired auxetic structure under compression and impact loading simulations were investigated. The studied auxetic structure was developed from a previous study and it was assigned 316 stainless steel material for all simulations. The compression loading simulation was conducted with compression velocities of 100 m/s, 80 m/s, 60 m/s, 40 m/s, and 20 m/s while the impact loading simulation was conducted with impact velocities of 50 m/s and 5 m/s. Two orientations of the structure were examined, and the results showed that orientation 1 had better energy absorption capabilities, with a more uniform distribution of stress and deformation compared to orientation 2. Further analysis revealed that the structural design of orientation 2 resulted in localised deformation and higher peak stress. Future studies could explore the potential for scaling up the structure, examining the deformation modes and optimising the material to enhance its energy absorption capabilities. The findings of this study can contribute to the development of lightweight and efficient energy-absorbing structures for various applications, including impact protection and crashworthiness.